A study on determinants of saving in Malaysia / Syamsuriana Sidek - Sidek, Syamsuriana (2011)
Understanding the nature of savings behavior is critical in designing policies to promote savings and investment. Given the differences in the economic environment of the developing and industrial countries there should be substantial variation in the household behavior. Savings play an important role in economic development. Growth theories have shown that savings is a necessary ingredient to finance investment which will enhance a country’s productivity. Thus, it would be important to look at the determinants of people’s saving to fully understand economic growth. The study will be used time-series regression method to see the relationships between dependent and independent variables. Saving is used as dependent variable and income, rate of return, inflation and consumption are used as independent variables